The Dirt: Industrial Disease and Conflict at St. Lawrence, Newfoundland - Rennie, Rick (Fernwood, 2008)
In the cemeteries of St. Lawrence and several neighbouring towns on the south coast of Newfoundland lie the remains of some 200 workers, killed by the dust and radiation that permeated the area’s fluorspar mines. The Dirt chronicles the many forces that created this disaster and shaped the response to it, including the classic ‘jobs or health’ dilemma, the contentious process of determining the nature and extent of industrial disease and the desire of employers to ‘externalize’ the costs of production onto workers and communities. Central to the account is the persistent effort by workers, women in the community and other activists to gain recognition of health hazards in the mines, their effects on workers and to obtain adequate compensation for victims and their families. –Publisher's description. Contents: Origins of a disaster: working conditions and labour relations in the 1930s – Protest and retreat: the war years – Industry revival, increasing hazards and the recognition of sislicosis, 1946-1956 – More deadly perils: radiation and cancer – "The truly ghastly total" and the lack of compensation coverage – Mounting protest, industry closure, and the legacy of the past.
https://fernwoodpublishing.ca/book/the-dirt
Keywords: Aspect sanitaire; Diseases; Employees; Employees Diseases; Employees Health and hygiene; Fluorspar industry; Health and hygiene; Health and hygiene. Mining; Health aspects; Industrie; Maladies; Mineral dusts; Miners; Newfoundland and Labrador; Newfoundland and Labrador St. Lawrence; Newfoundland and Labrador. Calcium Fluoride; Newfoundland and Labrador. Occupational Diseases; Newfoundland and Labrador. Silicosis; Personnel; St. Lawrence. Fluorite; St. Lawrence. Fluorspar industry; St. Lawrence. Mineral dusts; St. Lawrence. Miners; St. Lawrence. Mineurs; Terre-Neuve-et-Labrador; Toxicologie; Toxicology; Toxicology. Miners

Labour Organization and Unions - Rennie, Rick; Botting, Ingrid Marie; Inglis, Gordon (Newfoundland and Labrador Heritage, 1998)
Until well into the 20th century, Newfoundland and Labrador's primary economic activity was in the fisheries. Most of the workforce was in the inshore cod fishery, a small-boat operation in which family enterprises caught, split, salted and dried the fish to produce a finished product that was traded to a merchant. Fishers were not wage workers but commodity producers, like farmers. Even in the Labrador and Grand Banks fisheries and the annual seal hunt, the workers were treated as independent contractors, paying for their own gear and supplies and receiving shares rather than wages. –Introduction

A Memoir of the Spanish Civil War: An Armenian-Canadian in the Lincoln Battalion - Stephens, D. P. (Douglas Patrick) (Canadian Committee on Labour History, 2000)
A Memoir of the Spanish Civil War is one man's bittersweet account of fighting with the International Brigades against the forces of General Francisco Franco in Spain from 1936 to 1939. Douglas Patrick (Pat) Stephens was born in Armenia in 1910 and emigrated with his family to Canada in 1926. Like countless others, his dream of finding a new and more prosperous life was severely shaken by the onset of the Great Depression, and he turned to the Communist Party of Canada in an attempt to combat the political and economic deterioration which had gripped much of the world. Franco's attempt to overthrow by military force the republican government of Spain seemed to Pat Stephens the ideal opportunity to put his political convictions into action. Through his connections in the Communist Party, he became one of some 1400 Canadians, and 40,000 International Volunteers in all, who went to Spain. Many of the volunteers, including the Canadians, went to Spain against the laws and the wishes of their governments. Many of them never came back. Stephens' memoir, dictated to his wife Phyllis Stephens shortly before his death in 1987, puts a very human face on this strange and complex war. It is a portrait of political and moral conviction tinged by creeping disillusionment. It is also a compelling depiction of the strength, frailty, doubt, and courage which can result from the sometimes incongruous intersection of the personal and the political. A Memoir of the Spanish Civil War is a valuable contribution to our understanding of the conflict which immediately preceded World War II, and of Canada's role in that conflict. – Publisher's description
https://archive.org/details/memoirofspanishc0000step
Keywords: Civil War; 1936-1939; Ejército Popular de la República. Abraham Lincoln Battalion; History; Personal narratives; Canadian; Soldiers; Spain